Effect of heat-acclimatization on cycling time-trial performance and pacing - Racinais, S.; Periard, J. D.; Karlsen, A.; Nybo, L. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Purpose: To determine the performance and pacing effects of heat-acclimatization on outdoor cycling time-trials (TT, 43.4 km) in the heat. Methods: Nine experienced cyclists performed 3 TTs in hot ambient conditions (TTH, ~37ºC). The first TTH (TTH-1) in the heat was not preceded by any heat acclimatization whereas TTH-2 and TTH-3 were performed on the 6th and 14th days of training in the heat. Control TTs in cold condition (TTC, ~8ºC) were obtained pre and post the heat intervention. Results: There were no differences in TTCs pre and post intervention. Irrespective of climate and acclimatization status the cyclists initiated the first 20% of all TTs with similar power output, but during TTH-1 they subsequently had a marked decrease in performance and average power (256±18W) was lower than TTC (304±9W, p<0.05). However, this decrement was partly counteracted by 1 week of acclimatization (TTH-2: 280±19W) and further reduced after 2 weeks of acclimatization (TTH-3: 294±14W). The TTH-3 was performed with a similar speed (TTH-3 39.8±2.3 vs. TTC 39.4±2.0 km/h) and time (TTH-3 66±4 vs. TTC 66±3 min) than TTC. HR was higher during the first 20% of TTH-1 than in the other TTs (p<0.05), but was similar during the remaining TTs. Final rectal temperature was similar in all TTHs (40.2±0.4ºC, p=1.000) and higher than in TTC (38.5±0.6ºC, p<0.001). Conclusion: Cyclists initiate time-trials in the heat at a similar power output as in cold environments. When not heatacclimatized, power output dropped to maintain similar physiological responses. This drop is partly recovered after one week and close to normalized after two weeks of heat-acclimatization allowing for a similar performance as the lower air density in a hot environment allows for faster speed at a given power output.